2015
DOI: 10.1111/cdev.12340
|View full text |Cite
|
Sign up to set email alerts
|

Infants Learn Baby Signs From Video

Abstract: There is little evidence that infants learn from infant-oriented educational videos and television programming. This four week longitudinal experiment investigated 15-month-olds’ (N=92) ability to learn ASL signs (e.g., patting head for hat) from at-home viewing of instructional video, either with or without parent support, compared to traditional parent instruction and a no-exposure control condition. Forced choice, elicited production, and parent report measures indicate learning across all three exposure co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(14 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…There was one exception to the finding that contingency mattered: in both conditions, children imitated actions during tablet sessions (Figure c) and later remembered actions in the lab (Figure b). They did not need social contingency to learn novel actions from video, a result consistent with Krcmar's () finding that 21–24‐month‐olds learned actions from video more readily than words and with Dayanim and Namy's () finding that 15‐month‐olds learned symbolic gestures from video. These findings appear inconsistent with Nielsen et al .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…There was one exception to the finding that contingency mattered: in both conditions, children imitated actions during tablet sessions (Figure c) and later remembered actions in the lab (Figure b). They did not need social contingency to learn novel actions from video, a result consistent with Krcmar's () finding that 21–24‐month‐olds learned actions from video more readily than words and with Dayanim and Namy's () finding that 15‐month‐olds learned symbolic gestures from video. These findings appear inconsistent with Nielsen et al .…”
Section: Discussionsupporting
confidence: 83%
“…Infants imitate novel actions early in the second year (Meltzoff, ) and deferred imitation is often used to examine preverbal infants’ learning from media (Barr & Hayne, ; Krcmar, ). Furthermore, 15‐month‐old children can learn symbolic gestures from repeated viewings of pre‐recorded videos (Dayanim & Namy, ) at an age when they accept a broad range of symbolic forms in communication (e.g. words, pictures, gestures) (Namy, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dayanim and Namy showed that 15-month-olds could learn the meaning of sign language symbols after 3 weeks of watching a commercially available video 4 times per week. 24 However, children in a comparison study group whose parents used a book of sign language symbols to teach the content retained more knowledge about the symbols' meanings for a longer period of time.…”
Section: At What Age Can Infants and Toddlers Learn From Screens?mentioning
confidence: 99%
“…Nevertheless, Kabali et al observed that slightly older children liked to watch videos on YouTube and other video sharing websites. Dayanim and Namy found that children aged 15 months could learn signs for expressive communication from videos. However, young children preferred to interact more with the real world than watching videos.…”
Section: Introductionmentioning
confidence: 99%